Investigating operations networks: a research design. (2nd November 2004) - Beach, R.; Webster, M.
Current trends in the global business environment are increasingly leading to the development of vertically disintegrated operations networks for manufacture. Within such networks, the effective use of subcontract arrangements is key to competitive success. This paper explores the reasons for using external manufacturers. A framework is presented and the utility of this is considered in relation to theory and to empirical findings from an industry survey. It is argued that the use of subcontractors in the operations network is determined as much by the competitive environment as contemporary management doctrine. Moreover, this paper reasons that the ability of an enterprise to develop appropriate relationships with its suppliers may differ significantly depending on which of a number of contemporary manufacturing paradigms is adopted by the principal organisation. This notion is explored and propositions pertaining to the influence of the principal-supplier relationship on overall network design are developed. A research design capable of facilitating the investigation of these propositions is presented.